2018
DOI: 10.1126/science.aar7462
|View full text |Cite
|
Sign up to set email alerts
|

Dual-spindle formation in zygotes keeps parental genomes apart in early mammalian embryos

Abstract: At the beginning of mammalian life, the genetic material from each parent meets when the fertilized egg divides. It was previously thought that a single microtubule spindle is responsible for spatially combining the two genomes and then segregating them to create the two-cell embryo. We used light-sheet microscopy to show that two bipolar spindles form in the zygote and then independently congress the maternal and paternal genomes. These two spindles aligned their poles before anaphase but kept the parental ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 33 publications
7
100
0
1
Order By: Relevance
“…These observations aligned with previous indications that the maternal and paternal genomes are spatially segregated in zygotes (54,55) and remain so to a lesser extent as late as the 8-cell stage ( (25,26); fig. S8).…”
supporting
confidence: 91%
“…These observations aligned with previous indications that the maternal and paternal genomes are spatially segregated in zygotes (54,55) and remain so to a lesser extent as late as the 8-cell stage ( (25,26); fig. S8).…”
supporting
confidence: 91%
“…It was recently shown that in mice, the first zygotic mitosis occurs on two separate, and often parallel, spindles (Reichmann et al, 2018). If the mechanism of pronuclear membrane remodeling in C. elegans applies to vertebrates, then these two spindles may be separated by remnants of the pronuclear membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The number of direct unequal cleavage divisions at the zygote stage seems to be insufficient to account for all the observed haploid and uniparental cells at the eight-cell-stage embryos derived from fertilizations with damaged sperm. Because parental genomes still occupy distinct territories at the two-cell stage (37,38), uniparental and haploid cells may also be formed by unequal cleavages at this stage of development. The observation that frequently only half of the cells of eight-cell-stage embryos were haploid/uniparental may indicate heterogoneic cell divisions of two-cell-stage blastomeres.…”
Section: Discussionmentioning
confidence: 99%